Data engineering with Apache Spark, Delta Lake, and Lakehouse : create scalable data pipelines and networks that ingest, process, and store complex data /: create scalable data pipelines and networks that ingest, process, and store complex data. (2021) - Kukreja, Manoj
No abstract available